Ecological Psychology and Enaction Theory: Divergent Groundings - Heft, Harry (Frontiers in Psychology, 2020)
Both ecological psychology and enaction theory offer an alternative to long-standing theoretical approaches to perception that invoke post-perceptual supplemental processes or structures, e.g., mental representations, to account for perceptual phenomena. They both do so by taking actions by the individual to be essential for an account of perception and cognition. The question that this paper attempts to address is whether ecological psychology and enaction theory can be integrated into a stronger non-representational alternative to perception than either one can offer on its own. Doing so is only possible if most of the basic tenets and concepts of ecological psychology and enaction theory are compatible. Based on an examination of the role that sensations play within each approach; the manner in which each treats the concept of information; and how each conceptualizes an organism’s boundaries, it is concluded that a synthesis of the two approaches is not possible. Particular attention is paid to the concept of sensations, the limitations of which were an impetus for the development of ecological psychology.